Pancreatitis, hypereosinophilia and bilateral pulmonary infiltrates as presentation of acute Q fever. (September 2021) - Cancela Costa, A.; Chheang, C.; Thorens, O.; Lamy, O.; Prella, M.; Babaker, M.; Lamoth, F.; Greub, G.
Abstract: Q fever, caused by Coxiella burnetii, is a poorly recognized zoonotic infection given its polymorphic clinical presentation. The diagnosis should not be missed to treat in the acute phase and thus prevent major complications of the chronic phase. We describe a case of acute Q fever with pancreatitis, hypereosinophilia and pulmonary infiltrates.